57 Fatigue & facilities at kettering general hospital the importance of high-quality rest to maximise the performance of junior doctors and ensure patient safety. (16th November 2020) - Silva, Geeth; Yam, Aiken; Court, Jessica; Imtiaz, Rabia
Abstract : Introduction: Junior doctors are increasingly working in an overstretched NHS. In 2018 Kettering General Hospital (KGH) was awarded £60, 800 of government funds to create high-quality rest facilities and improve junior doctor wellbeing. Methods: Through auditing doctors working at KGH, alongside consulting senior management, a project initiation document was constructed to spend this money. From November 2019 to June 2020 £46, 275 was spent on creating new rest facilities, including separate sleeping and working areas. Furthermore, the purchase of modern furniture and equipment met the functional needs of busy junior doctors. One month after the completion of the project, the team conducted a post-action review by re-auditing how the changes impacted morale, wellbeing and quality of patient care. Results: Now, the majority of doctors are happy with the current rest areas on offer at KGH (60%), and a majority feel that they will use the on-call room area (63%). Overall, the feedback from both interviews and the JDF was positive and, the renovation improved morale and wellbeing. There was an increased ability to take breaks. However, the majority of doctors are still not exception-reporting missing breaks: 79% (2019), 74% (2020). Lessons Learnt: Whilst improved rest facilities were welcomed, this report recommends the maintenance of increased staffing levels and fatigue facilities during the recovery phase of COVID-19. The remaining £14, 524.38 should be directed at creating shower facilities, upgrading computer hardware and sustaining the quality of KGH fatigue facilities. Lastly, the rate of exception-reporting must be increased through improving awareness, exploring alternative methods and supporting the action when necessary. The continual investment into rest facilities not only ensure workforce wellbeing but undoubtedly translates into the safety of our patients.